Influence of AlxGa1−xN barrier layer thickness and p-GaN gate characteristics on the threshold voltage of p-GaN/AlGaN/GaN high electron mobility transistors - Bang-zhi Xiao; Yin-shui He; Wen-bo Xiao (AIP Advances)
In this research work, the pivotal role of threshold voltage (Vth) in the performance optimization of enhancement-mode (E-mode) AlGaN/GaN-based high-electron-mobility transistors (HEMTs) is explored. We report the development of an E-mode AlGaN/GaN HEMT through the strategic design of the AlxGa1−xN barrier layer and p-type GaN gate. The modulation of Vth is demonstrated to be highly responsive to variations in the thickness and aluminum mole fraction of the AlxGa1−xN barrier layer, with a decrease in these parameters correlating with an increase in Vth. Moreover, we have established that augmenting the thickness and doping concentration of the p-GaN layer can lead to a further enhancement of Vth. However, this improvement is counterbalanced by a reduction in transconductance. Consequently, we propose an optimized p-GaN/AlGaN/GaN HEMT design, which exhibits a Vth of up to +1.96 V and a peak transconductance of 282 mS/mm. Our findings elucidate the intricate relationship between the barrier and gate layers and their influence on HEMT device performance, providing a foundation for the design of high-performance E-mode AlGaN/GaN HEMTs.